Enhanced transdermal permeability of piroxicam through novel nanoemulgel formulation - Dhawan, Bhavna; Aggarwal, Geeta; Harikumar, SL (International Journal of Pharmaceutical Investigation)
Background: Piroxicam is a non-steroidal anti-infl ammatory drug belongs to BCS class II drugs having poor solubility and is associated with a number of undesirable side-effects on the stomach and kidneys in addition to gastric mucosal damage. Aim: The present work was to develop and characterize nanoemulgel formulation as transdermal delivery system for poorly water soluble drug, in order to overcome the troubles associated with its oral delivery and to circumvent the need of chemical penetration enhancers, which are responsible for causing skin irritation in transdermal drug delivery. Materials and Methods: Different nanoemulsion components (oil, surfactant and co-surfactant) were selected on the basis of solubility and emulsifi cation ability. Pseudoternary phase diagrams were constructed using aqueous titration method to fi gure out the concentration range of components. Carbopol 934 was added as gel matrix to convert nanoemulsion into nanoemulgel. Drug loaded nanoemulsions and nanoemulgels were characterized for particle size, transmission electron microscopy, viscosity, conductivity, spreadability, rheological behavior, permeation studies using Wistar rat skin and stability studies. Transdermal permeation of piroxicam from nanoemulgels was determined by using Franz Diffusion cell. Results: The optimized nanoemulgel (BG6) contained 10% oleic acid as oil, 35% tween 80 and ethanol as surfactant co-surfactant mixture, 55% water, 0.5% drug and 0.5% w/w carbopol. The ex vivo permeation profi le of optimized formulation was compared with nanoemulsion and marketed formulation (Feldene®). Nanoemulgel showed higher (P < 0.05) cumulative amount of drug permeated and fl ux and signifi cantly less drug retained along with less lag time than marketed formulation. Conclusion: The results indicate that nanoemulgel formulation can be used as a feasible alternative to conventional formulations of piroxicam with advanced permeation characteristics for transdermal application.
Keywords: Carbopol 934; nanoemulsion; permeation; piroxicam; ternary diagram